PENGUNGKAPAN PENDAPATAN DANA NON HALAL MENURUT PSAK 109 PADA PT. BANK MUAMALAT INDONESIA TBK. PERIODE 2019-2021 - Astuti, Widya; Arafah, Muh.; Hasbi, Hartas (IAIN BONE, 2024)
AbstractThis study aims to assess the alignment of non-halal fund revenue with PSAK 101 and PSAK 109 at PT. Bank Muamalat Indonesia Tbk. The researcher used a qualitative descriptive technique, drawing on secondary data from the PT Financial Report. Bank Muamalat Indonesia Tbk for the period 2019-2021. The data analysis process consisted of three steps: data reduction, data presentation, and drawing conclusions.The discoveries demonstrate that the detailing of non-halal support income complies with PSAK 101, as appeared within the Source and Utilize of Kind Stores Report, and PSAK 109, as shown within the Notes to the Monetary Report of Bank Muamalat Indonesia Tbk for 2019-2021. In any case, there are discrepancies within the account title as displayed within the budgetary report, both in terms of finance sum and clarification. Assist, revelations are made within the reports of sources and generous stores, where PSAK 101 mandates that the substance uncovers the reasons for the utilization of non-halal receipts within the notes to the monetary explanations. The ultimate adjust of non-halal salary, which shapes portion of the generous finance, is spoken to as a obligation, showing up within the prompt liabilities area and mostly within the other liabilities segment.Â The Bank Muamalat Indonesia Tbk financial report, which is available in CALK, clearly discloses non-halal income. The Source of Use of Virtuous Giro Funds is the term used to describe the non-halal income stated in CALK. Overall, Bank Muamalat Indonesia Tbk has revealed non-halal income in accordance with PSAK 101 addressing the reporting of financial statements and PSAK 109 about non-halal income, albeit the specific amount per item in each transaction has not been defined.AbstrakPenelitian ini bertujuan untuk menguji kepatuhan pengelolaan dana non halal Bank Muamalat terhadap standar PSAK 101 dan PSAK 109. Penulis menggunakan pendekatan deskriptif kualitatif dan data sekunder yang diambil dari Laporan Keuangan Bank Muamalat periode 2019-2021. Analisis data dilakukan melalui tiga langkah utama: mereduksi data, menyajikan data, dan menyimpulkan hasil.Hasil penelitian menunjukkan bahwa Bank Muamalat Indonesia Tbk telah mengungkapkan pendapatan dana non halal sesuai dengan ketentuan yang terdapat dalam PSAK 101 dan PSAK 109. Pengungkapan ini terdapat dalam Laporan Sumber dan Penggunaan Dana Kebajikan serta Catatan atas Laporan Keuangan selama periode 2019-2021. Lebih lanjut, dalam pengungkapan pada laporan sumber dan penggunaan dana kebajikan, Bank Muamalat Indonesia Tbk telah mengikuti ketentuan PSAK 101 dengan mengungkapkan penyebab penggunaan penerimaan non halal dalam catatan atas laporan keuangan.Bank Muamalat Indonesia Tbk mengungkapkan pendapatan non halal melalui Laporan Keuangan yang disajikan dalam Catatan Atas Laporan Keuangan (CALK). Meskipun rincian jumlah per transaksi belum ditemukan secara spesifik, secara umum, Bank Muamalat Indonesia Tbk telah memenuhi ketentuan PSAK 101 dan PSAK 109 dalam mengungkapkan pendapatan non halal sesuai dengan standar penyajian laporan keuangan yang berlaku..